Parallel Services Intelligent Systems of Digital Twins and Metaverses for Services Science - Li, Lefei; Wang, Fei-Yue. (Cham : Springer International Publishing : Imprint: Springer, 2023)
By incorporating the latest advancement in complex system modeling and simulation into the service system research, this book makes a valuable contribution to this field that will lead service innovation and service management toward the digital twin and metaverse. It covers important topics such as computational experiments and parallel execution of a parallel service system, the modeling of artificial service systems, semi-parallel service systems, parallel service, and digital twin/metaverse. It also provides a unified framework for realizing a parallel service system that demonstrates the capabilities or potentials of adopting digital twin and metaverse. In addition, the book contains numerous solutions to real-world problems, through which both academic readers and practitioners will gain new perspectives on service systems, and learn how to model a parallel service system or how to use the model to analyze and understand the behaviors of the system. For academic readers, it sheds light on a new research direction within the service science/engineering domain made possible by the latest technologies. For practitioners, with the help of methods such as Agent-based Modeling and Simulation, the book will enable them to enhance their skills in designing or analyzing a service system.
Keywords: Production management; Service industries; Application software; Artificial intelligence; User interfaces (Computer systems).; Human-computer interaction; Operations Management; Services; Computer and Information Systems Applications; Intelligence Infrastructure; User Interfaces and Human Computer Interaction